De volta às trincheiras: o revisionismo histórico paraguaio e a Guerra contra a Tríplice Aliança (1870-1930) - Queiróz, Silvânia de (2018)
The writing of history is a complex process, involving many aspects, especially ideological, political and economic. After the War of the Triple Alliance with the Republic of Paraguay [1864-70], this country was destroyed and power was found in the hands of the victorious alliance forces, supported by legionaries, Paraguayans who fought against their country. After the war, the historiographical and cultural representations of the victors became hegemonic in Paraguay. They did not prevent the existence of disviews on Paraguayan history in general, and war, in particular. Before the war, there was an intellectual elite in Paraguay that reflected and wrote about the country, directly or indirectly. Among these prewar intellectuals we can highlight Alfred Demersay, Carlos Antonio López, J.R.Rengger, Manuel Pedro de Peña, Mariano Antonio Molas, Juan André Gelly, Francisco Wisner, among many others. In the post-war period, the so-called generation of the nineteenth century, which was one of the most important promotions of intellectuals in the country, was one of the first groups of thinkers dedicated to the study of Paraguayan culture and history. Among them were Blas Garay (1873-1899), Cecilio Báez (1862-1941), Juan Emiliano O'Leary (1879-1969), Manuel Domínguez (1868-1935), Juan Silvano Godoi (1846-1926), Gregory Benites (1834-1909), Fulgencio Moreno (1872-1933), Arsenio López Decoud (1867-1945), Ignacio Pane (1879-1920), Eligio Ayala (1879-1930), Manuel Gondra (1871-1927) and Jose According to Decoud (1848-1909). The so-called Generation of the Nineties played a central role in the construction of Paraguayan historiography. For many decades the hegemonic historiographical view in Paraguay was the vision of the Aliancistas, where the fault of the conflict was attributed solely to the "tyrant" Solano Lopez; Paraguay would be a country without glories, marked by despotism and that the war would have contributed to the "introduction" of civilization in Paraguay. On the other hand, some of the abovementioned intellectuals began a rescue movement of Paraguayan history and nationalism, among them Blas Garay, Juan Silvano Godoi, Juan Emiliano O'Leary and Manuel Domínguez would have exalted the deeds of the Paraguayan people long before the emergence of lopismo positive in 1930. We can see that, since the end of the war, there was a deaf movement of sympathy toward Marshal Francisco Solano López, among the population of the country. In a visit to Paraguay in 1887-8, the liberal-Mitrista politician, Estanislao Zeballos, would declare, on the constitution already practically organic of the lopist movement, which explained how the revival of Paraguayan regressive atavistic tendencies. Through the works produced by the four intellectuals mentioned above, the school manuals and the postwar periodicals, we will analyze the beginning of historical revisionism and seek to understand how Paraguayan historiography was constituted, its influences, similarities and differences.